The wicked sister - Dionne, Karen (G.P. Putnam's Sons, 2020)
"From the bestselling and award-winning author of The Marsh King's Daughter comes a startling novel of psychological suspense as two generations of sisters try to unravel their tangled relationships between nature and nurture, guilt and betrayal, love and evil"--